Answer:
smaller x: -4
larger x: 1
Explanation:
We need to factor this. In order to do so, we need to find factor pairs of the coefficient of x^2 (which is 1 in this case) and of the constant (-4 in this case) such that they add up to 3.
Here, the factors of 1 are obviously just 1 and 1. The factors of -4 are (1, -4), (-1, 4), and (2, -2). Notice that 1 * 4 + 1 * (-1) = 3, so we know that our factor pair from 1 is (1, 1) and our factor pair from -4 is (-1, 4).
Then, we factor this quadratic into: (x - 1)(x + 4) = 0. Now, solve for x by setting each of these two factors equal to 0:
x - 1 = 0 ⇒ x = 1
AND
x + 4 = 0 ⇒ x = -4
So, the solutions are x = -4 and x = 1.
Hope this helps!